2018
DOI: 10.1002/pssa.201800531
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Characterization of Active Doping Concentration in Boron‐Doped Individual Si Nanocrystals

Abstract: Doping of Si nanocrystals (NCs) is essential to the photonic and photovoltaic applications. In this work, individual Si NCs on Si substrate are prepared by excimer laser crystallization technique. The doping effect of boron (B) atoms is characterized at the nanoscale by Kelvin probe force microscopy (KPFM) measurement. The KPFM signal of B-doped Si NCs is found opposite to that of intrinsic counterparts, indicating that active B doping is obtained. Moreover, the surface potential is reconstructed from KPFM ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…As a consequence, only qualitative data, such as the surface’s polarity, after the tribocharging process can be acquired. It has been attempted by Xu et al to resolve the qualitative KPFM data to calculate the number of charges present on semiconductor surfaces, 21 but for insulators, such methods are unprecedented.…”
Section: Characterizing Triboelectric Chargingmentioning
confidence: 99%
“…As a consequence, only qualitative data, such as the surface’s polarity, after the tribocharging process can be acquired. It has been attempted by Xu et al to resolve the qualitative KPFM data to calculate the number of charges present on semiconductor surfaces, 21 but for insulators, such methods are unprecedented.…”
Section: Characterizing Triboelectric Chargingmentioning
confidence: 99%
“…In the past decade, EFM/KPFM has been successfully used to study the injection and retention of trapped charges in inorganic films, [ 16,25,45,46,52–57 ] polymer electrets, [ 47,58–60 ] organic small molecules, [ 42,44 ] the composition of polymer and organic semiconductors, [ 27,41,43 ] nanostructure, [ 48–51,61–78 ] double‐barrier CeO 2 /Si/CeO 2 /Si structures, [ 79 ] DNA molecules, [ 39–80 ] and thin‐film transistors. [ 81–86 ] For example, Heim et al proved that EFM is a useful technique to study the electronic properties of an organic monolayer island at the nanometer scale and found that both carriers are delocalized over the whole island in crystalline monolayer islands, while carriers stay localized at their injection point on a disordered monolayer.…”
Section: Introductionmentioning
confidence: 99%